2015
DOI: 10.1097/scs.0000000000001665
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Extractions in High-Risk Patients Under Bisphosphonate Therapy and Previously Affected With Osteonecrosis of the Jaws

Abstract: Trauma during dental surgery is a predisposing factor for medication-related osteonecrosis of the jaws (MRONJ). There are no specific guidelines for the management of dental extractions in patients under bisphosphonate therapy (BPT). The authors proposed in 2013 a successful protocol for tooth extractions in patients under BPT supported by Nd:YAG low-level laser therapy (LLLT). The aim of this study was to validate the safety and efficacy of this protocol reporting the data related to its application in a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 24 publications
2
45
0
1
Order By: Relevance
“…However, multiple studies suggested a benefit from PBM in the management of medication-related osteonecrosis of the jaw (MRONJ) [98101]. Vescovi et al proposed a prophylactic protocol including PBM for reducing BRONJ incidence following tooth extractions [102]. Luomanen et al reported about a successful treatment of a patient with MRONJ using Nd:YAG laser [103].…”
Section: Pbm For the Management Of Orofacial And Neck Complications Omentioning
confidence: 99%
“…However, multiple studies suggested a benefit from PBM in the management of medication-related osteonecrosis of the jaw (MRONJ) [98101]. Vescovi et al proposed a prophylactic protocol including PBM for reducing BRONJ incidence following tooth extractions [102]. Luomanen et al reported about a successful treatment of a patient with MRONJ using Nd:YAG laser [103].…”
Section: Pbm For the Management Of Orofacial And Neck Complications Omentioning
confidence: 99%
“…35 These facts could explain the beneficial effect of LLL therapy when it is associated with the conventional treatment of MRONJ. 12,22 The laser parameters, including the energy that is delivered, power density, pulse duration, appropriate treatment, timing and repetition, and the appropriate anatomical location must be adequate to create a biostimulatory effect. 23 In this case report, we used the laser emitting GaAlAs at a wavelength of 808 nm with an energy density of 19.4 J/ cm 2 /point (8 points) for a period of 2 months (13 sessions).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is particularly relevant due to its possible application in the treatment of patients with impaired healing processes, including those treated with bisphosphonates or other anti-resorptive/angiogenic drugs, those affected by diabetes, or those treated with corticosteroids. 16,17 Apart from patients with systemic diseases or those taking drugs that may interfere with the healing process, the notion that laser light penetrates beyond the irradiated surface, even when used in a low-level energy mode, has implications in other fields of dentistry.…”
Section: Discussionmentioning
confidence: 99%